2017
DOI: 10.5551/jat.37010
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Uric Acid Levels with Leg Ischemia in Patients with Peripheral Arterial Disease after Treatment

Abstract: Aim: We investigated the relationships of serum uric acid levels with the progression of atherosclerosis in patients with peripheral arterial disease (PAD) after treatment.Methods: Subjects were male patients diagnosed with PAD. Atherosclerosis at the common carotid artery was evaluated based on its intima-media thickness (IMT). Leg arterial flow was evaluated by measuring ankle-brachial index (ABI) and exercise-induced decrease in ABI.Results: Among various risk factors including age, blood pressure, adiposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Some studies found that in patients with hyperuricemia, the accumulation of uric acid and activation of xanthine oxidoreductase may induce inflammation and increase oxidative stress, accelerates atherosclerotic progression, and promote the progression of PAD. 13 In a study of 508 patients with T2DM, Tseng found uric acid levels were higher in patients with PAD than in those without, suggesting elevated uric acid level is a significant and independent risk factor for PAD in patients with T2DM. 9 In Tseng’s study, some patients were not elderly, while they obtained the same conclusion.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies found that in patients with hyperuricemia, the accumulation of uric acid and activation of xanthine oxidoreductase may induce inflammation and increase oxidative stress, accelerates atherosclerotic progression, and promote the progression of PAD. 13 In a study of 508 patients with T2DM, Tseng found uric acid levels were higher in patients with PAD than in those without, suggesting elevated uric acid level is a significant and independent risk factor for PAD in patients with T2DM. 9 In Tseng’s study, some patients were not elderly, while they obtained the same conclusion.…”
Section: Discussionmentioning
confidence: 98%
“…Uric acid is the final product of purine metabolism. In recent years, several population‐based studies have reported an association between serum uric acid (SUA) levels and increased risk of cardiovascular (CV) disorders such as hypertension, 1 myocardial infarction, 2 stroke, 3 peripheral arterial disease, 4 and sudden cardiac death 5,6 . Despite the fact that a continuous relationship between SUA and all‐cause and CV mortality has been suggested by many studies, more recently, data from the URRAH study (Uric Acid Right for Heart Health), allowed us to identify prognostic cut‐off values for major adverse events 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“… 25 Sotoda et al found that sUA levels are associated with the degree of leg ischemia in patients with peripheral arterial disease (PAD). 26 However, the gender differences in the association between sUA and arteriosclerotic cardiovascular risk among type 2 diabetes mellitus patients have been rarely studied.…”
Section: Discussionmentioning
confidence: 99%